Adults with repaired tetralogy: low mortality but high morbidity up to middle age. Issue 1 (1st March 2017) - Dennis, Mark; Moore, Ben; Kotchetkova, Irina; Pressley, Lynne; Cordina, Rachael; Celermajer, David S
Abstract : Objective: Survival of patients with repaired tetralogy of Fallot (rToF) into young adulthood is very good. Concerns exist, however, over long-term morbidity and mortality as these subjects reach middle age. We aimed to assess survival and the prevalence of complications in patients with rToF seen in our Adult Congenital Heart Disease (ACHD) service. Methods: One hundred and sixty-eight consecutive patients with 'simple rToF', aged over 16 years, followed up at our tertiary-level ACHD service in Sydney, Australia since 2000, were included. We documented mortality and analysed the prospectively defined composite end points of (a) 'Serious adverse events', including death, heart failure hospitalisation and/or documented ventricular arrhythmia and (b) 'Adverse events' inclusive of the above and endocarditis, atrial arrhythmia, defibrillator and/or pacemaker implantation. Results: Mean age at the last follow-up was 34±12 years, and 55% were men. There were 10 (6%) deaths, and 26 patients (16%) experienced a 'serious adverse event'. Fifty-one patients (30%) experienced an 'adverse event' and 29 patients had atrial arrhythmias. One hundred and one (61%) patients had at least one pulmonary valve replacement. By age 40 years, 93% were free of serious adverse events, and 83% were free of any adverse event. By age 50 years, only 56% had not had an adverse event. Older age and history of atrial arrhythmia were predictive of serious adverse events. Conclusion: Survival into mid-adulthood in patients with rToF is very good; however, a substantial number of survivors have adverse events by the age of 50 years.